Systematic Literature Review: The Effectiveness of Flipped Classroom in Chemistry Education to Enhance Students’ Competencies - Tiktik Mustika Budhi; Wiji Wiji; Sri Mulyani (Journal of Natural Science and Integration, 2026)
The Flipped Classroom (FC) model has gained increasing attention in chemistry education as an innovative approach to address challenges related to low conceptual understanding, limited student engagement, and the need to develop higher-order thinking skills. This study employs a Systematic Literature Review (SLR) guided by the PRISMA 2020 framework to systematically identify, screen, and synthesize relevant studies published between 2016 and 2026. A total of 31 peer-reviewed articles were selected and analyzed using thematic synthesis and cross-study comparative analysis to provide a comprehensive overview of FC implementation in chemistry education. The findings indicate that the FC model generally has a positive impact on students' competencies across cognitive, affective, and psychomotor domains. The cognitive domain shows the greatest improvement, particularly in conceptual understanding, problem-solving, and higher-order thinking skills. In the affective domain, FC enhances students' motivation, engagement, and self-confidence, while in the psychomotor domain, it supports the development of laboratory skills, experimental procedures, and inquiry-based practices. The implementation of FC is most prevalent in general and organic chemistry but has increasingly expanded into other sub-disciplines, including physical chemistry, biochemistry, environmental chemistry, and laboratory-based learning. However, the effectiveness of FC is highly context-dependent and influenced by factors such as instructional design quality, technological accessibility, and students' readiness for self-directed learning. Several studies also report inconsistent findings and highlight limitations, including the predominance of short-term research designs and the lack of evidence regarding long-term learning retention. Overall, the FC model demonstrates strong potential to enhance the quality of chemistry education. Nevertheless, its successful implementation requires careful alignment between pre-class materials, in-class activities, and assessment strategies. Future research should prioritize longitudinal studies and more inclusive educational contexts to strengthen the evidence base for sustainable and scalable FC practices. Keywords: flipped Classroom, chemistry education, systematic literature review, student competencies